Slag Resistance of Al2O3–MgO Refractory Castables in Different Environmental Conditions. Issue 10 (14th June 2013) - Sako, Eric Y.; Braulio, Mariana A. L.; Luz, Ana Paula; Zinngrebe, Enno; Pandolfelli, Victor C.; Rigaud, M.
<x xml:space="preserve">Abstract</x> Although the corrosion performance of spinel‐containing castables has been extensively investigated in recent years, no previous studies accessed the different conditions present in the ladle bottom. In this region, strong variations in the atmospheric environment are often detected, which could drastically change the interactions between refractory and molten slag. In the present work, the main corrosion mechanisms of an alumina–magnesia castable in two environmental conditions (oxidizing – pO2 = 0.21 atm—or reducing – pO2 = 10−15 atm— atmosphere) were evaluated by means of scanning electron microscopy and EDS analyses of the corroded samples and thermodynamic simulations. The attained results showed that the slag penetration was suppressed in the presence of oxygen due to the precipitation of a great amount of calcium monoaluminate (CA) crystals as the refractory interacted with slag. Conversely, the CA phase was not stable under reducing conditions and, therefore, many more refractory components (Al2O3, MgO, and MgAl2O4) had to be dissolved to precipitate calcium dialuminate (CA2) by reacting with infiltrating slag. Thus, besides providing a suitable and more realistic understanding of the castable performance in service conditions, the results also indicated that the prediction of the environmental conditions is of utmost importance for the design of high performance refractories.